PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PESAWAT SEDERHANA KELAS VIII SMP NEGERI 4 TEBING TINGGI - Nurjanah, Siti; Ma'aruf, Zuhdi; Rahmad, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research isto increase student learning outcomes by the learning cycle 7e model on simple machine materials in class VIII state Junior high school 4 Tebing Tinggi. The research method be used in this study is Quasi experimental with Two-group post-test-only design,that uses two groups. This group consist of an experimental group and group control. The Instrument to collecting data in this study uses written test of students cognitive learning outcomes as a posttest with an objective form.The results of the data analysis for the average students grade on an experiment that uses the learning cycle 7e are higher than the control classusing conventional learning. The percentage of the average value of the experimental class students 74% with a high category while thecontrol class 64% with enough categories. Variations in the number of data values for the experimental class and the control class can be see from the standard deviation of the student’s posttest results. The standard deviation of the control class 9,845 while the experimental class is 9,307 so that variation in the values of the control class tends to be higher than the experimental class with a differences of 0,538. Based on inferential analysis, there are significant differences in student’s cognitive learning outcomes between classes applying the learning on simple plane material. Therefore, both descriptively and inferentially, the use of the learning cycle 7emodelis more effective to improve student learning outcomes on simple machine material in class VIII of SMPN 4 Tebing Tinggi.KeyWords : Learning Cycle 7e, Learning Outcomes, Simple Machine, Two-Group Post-Test-Only Design.